2014
DOI: 10.1016/j.stem.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-Receptor-Expressing Mesenchymal Stromal Cells Represent the Main Source of Bone Formed by Adult Bone Marrow

Abstract: SUMMARY Studies of the identity and physiological function of mesenchymal stromal cells (MSCs) have been hampered by a lack of markers that permit both prospective identification and fate mapping in vivo. We found Leptin Receptor (LepR) is a marker that highly enriches bone marrow MSCs. Approximately 0.3% of bone marrow cells were LepR+, 10% of which were CFU-F, accounting for 94% of bone marrow CFU-F. LepR+ cells formed bone, cartilage, and adipocytes in culture and upon transplantation in vivo. LepR+ cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

71
1,377
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,126 publications
(1,505 citation statements)
references
References 52 publications
71
1,377
2
2
Order By: Relevance
“…These fibroblast-like reticular cells have been generically defined in mice by expression of common markers (leptin receptor and CD140a), and the secretion of large amounts, at least by a substantial fraction of this population, of regulatory factors such as interleukin-7 (IL-7), stem cell factor, and CXCL12. 31,[47][48][49][50] For this feature, they were first visualized in the CXCL12-GFP knock-in mouse model and termed CXCL12-abundant reticular (CAR) cells. 51 Multiple studies have now shown that CAR cells are fundamental players in the regulation of specific and very distinct stages of hematopoiesis.…”
mentioning
confidence: 99%
“…These fibroblast-like reticular cells have been generically defined in mice by expression of common markers (leptin receptor and CD140a), and the secretion of large amounts, at least by a substantial fraction of this population, of regulatory factors such as interleukin-7 (IL-7), stem cell factor, and CXCL12. 31,[47][48][49][50] For this feature, they were first visualized in the CXCL12-GFP knock-in mouse model and termed CXCL12-abundant reticular (CAR) cells. 51 Multiple studies have now shown that CAR cells are fundamental players in the regulation of specific and very distinct stages of hematopoiesis.…”
mentioning
confidence: 99%
“…A previous study showed that LepR + cells in bone marrow are the major subset of stem/progenitor cells contributing to bone formation and the maintenance of the haematopoietic cell niche in adults (Zhou et al., 2014). We investigated a large proportion of LepR + cells displaying a senescence phenotype in aging mice, and TMP significantly decreased p16 + ‐expressing LepR + cells and instead increased BrdU + ‐labelled LepR + cells (Figure 2a–c).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that LepR + MSPCs is essential in maintaining the HSC niche (Zhou et al., 2014). To gain more insight into the regulatory effect of TMP on the bone marrow microenvironment and LepR + MSPCs in aging mice, we sorted LepR + MSPCs from 4‐ and 20‐month‐old mice treated with or without TMP and analysed the expression of genes that regulate HSC maintenance and attraction (Cxcl12, c‐kit ligand, angiopoietin‐1, interleukin‐7 and vascular cell adhesion molecule‐1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations